2021
DOI: 10.3390/molecules26102885
|View full text |Cite
|
Sign up to set email alerts
|

Physico-Chemical Properties of Inorganic NPs Influence the Absorption Rate of Aquatic Mosses Reducing Cytotoxicity on Intestinal Epithelial Barrier Model

Abstract: Noble metals nanoparticles (NPs) and metal oxide NPs are widely used in different fields of application and commercial products, exposing living organisms to their potential adverse effects. Recent evidences suggest their presence in the aquifers water and consequently in drinking water. In this work, we have carefully synthesized four types of NPs, namely, silver and gold NPs (Ag NPs and Au NPs) and silica and titanium dioxide NPs (SiO2 NPs and TiO2 NPs) having a similar size and negatively charged surfaces. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 60 publications
1
1
0
Order By: Relevance
“…The results obtained were in line with those reported by other authors for the human tumor Caco-2 colon adenocarcinoma cell line [ 94 , 95 , 96 ]. A study conducted by Gomaa [ 15 ] on the colon carcinoma cell line showed toxicity at much lower concentrations, the IC50 value of the tested AgNPs had a range between 2.3 and 2.2 µg/mL.…”
Section: Discussionsupporting
confidence: 92%
“…The results obtained were in line with those reported by other authors for the human tumor Caco-2 colon adenocarcinoma cell line [ 94 , 95 , 96 ]. A study conducted by Gomaa [ 15 ] on the colon carcinoma cell line showed toxicity at much lower concentrations, the IC50 value of the tested AgNPs had a range between 2.3 and 2.2 µg/mL.…”
Section: Discussionsupporting
confidence: 92%
“…We used an OSMOMAT 070 osmometer for the measurement of osmolality of our solutions as vapor pressure method is appropriate for determination of osmolality or molecular weight [22][23][24][25]. In vitro cytotoxicity experiments were carried out on Caco-2 human colorectal adenocarcinoma cells as a general model cell line, but also as indicators of the susceptibility of the gastrointestinal tract as they morphologically represent the intestinal epithelium [26,27]. The cytotoxicity was assessed by MTT and Neutral Red assays which are widely used in vitro techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Due to their high surface-to-volume ratio, nanosized structures exhibit different physicochemical properties compared to bulk structures [91]. Consequently, NPs demonstrate greater activity in various biological applications [92].…”
Section: Plant-extract-based Npsmentioning
confidence: 99%